The Eurasian beaver handbook : ecology and management of castor fiber /: ecology and management of castor fiber. (2016) - Campbell-Palmer, Roisin; Gow, Derek; Schwab, Gerhard; Halley, Duncan; Gurnell, John; Girling, Simon; Lisle, Skip; Campbell, Ruairidh; Dickinson, Helen; Jones, Simon; Parker, Howard; Rosell, Frank
No abstract available